Perspectives on nanofiber dressings for the localized delivery of botanical remedies in wound healing - Bhullar, Sukhwinder Kaur; Buttar, H.S. (AIMS Press, 2017)
Based on their antiseptic and anti-inflammatory properties, plant-derived remedies and herbal products have been used since ancient times for wound and burn cure as well as for treating chronic skin diseases like dermatitis and eczema. Biocompatible and biodegradable polymer nanofiber devices are currently fabricated using sophisticated engineering techniques. Such nanofiber structures have proven efficacious for the localized delivery of therapeutic agents for the treatment of wounds due to their unique physical-chemical properties such as large surface-area-tovolume ratio, high porosity, improved cell adherence, cellular proliferation and migration, as well as controlled in vivo biodegradation rates. The remit of this communication is to highlight the methodology used for the fabrication of nanofiber mats and dressings for the localised delivery of herbal products and plant-derived ingredients for wound healing. © 2017 Sukhwinder K. Bhullar, et al.
Keywords: Biodegradable dressings and mats; Fabrication of nanofiber dressings; Localised delivery of botanical remedies; Wound healing